EVALUATION OF FORMAT AND SECURITY OF DENTAL ELECTRONIC MEDICAL RECORD SYSTEMS IN GENERAL HOSPITAL BASED ON LEGISLATION - Erdianto Setya Wardhana; Suryono Suryono; Ari Hernawan; Lukito Edi Nugroho (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Electronic medical records in dentistry are the latest implementation in the health sector, especially dental health history to the services needed by patients by health care facilities and affect the format of dental, medical records and electronic medical record security systems. This study aimed to review the completeness of the medical record format and the electronic medical record security system of the dental polyclinic of the General Hospital in Batam City. Method: This study used a descriptive cross-sectional observational design with two samples. Processing data in the form of tables and texts and conclusions as a result of research. Result: The results showed incomplete dental electronic medical record formats at hospital A, such as patient identity, required medical data, odontogram, intraoral examination, and treatment chart, while Hospital B included patient identity, required medical data, intraoral analysis, treatment chart, and appendix. The two samples did not meet the integrity and non-repudiation aspects of the electronic medical record security system. Conclusion: According to the Indonesian Dental Medical Record Guidelines, both samples have an incomplete dental electronic medical record format and security system.